Amphibian diversity increases in an heterogeneous agricultural landscape - Guerra, Cecilia (2015)
As a group amphibians are the vertebrates most affected by anthropic activity, particularly by agriculture. The rapid advance of the agricultural frontier makes it important to identify the role of agroecosystems as habitat supply for amphibians. We analyzed the differences in amphibian assemblages and populations between habitats with different plant covers and different degrees of human intervention in northwestern Argentina. For three years we conducted 114 high frequency trap samplings to quantify abundance, specific composition and species richness of amphibian assemblages in three habitat types (lemon and sugarcane crops and secondary forest) of a piedmont agroecosystem of Tucumán province. Crops hosted more species and individuals than secondary forests, but the specific composition of forest was different from that of crops suggesting that they could be complementary. Although the assemblage abundance of every observation responded to climate, the strong effect of sampling year was not related to climatic factors suggesting that there might be long term fluctuations that were not analyzed. We also found that responses to agricultural practices were species specific, so no generalizations about these practices should be done. Our study shows that cultivated areas are not hostile environments for amphibians since they can lodge huge amphibian populations and that the occurrence of disturbances associated to agricultural practices is not necessarily reflected in a decrease in the abundance and richness of amphibians in the short term. However, our results also show that forested lands are necessary to lodge some specialist species which are very rare in the croplands. This suggests that environmental heterogeneity generated by the combination of natural and cultivated patches can increase biodiversity at landscape scale because this allows the coexistence of species related to either kind of environment.